2002
DOI: 10.1070/rc2002v071n07abeh000700
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral metal derivatives and exohedral fluorine derivatives of fullerenes

Abstract: The thermodynamic studies of fullerenes and their stable The thermodynamic studies of fullerenes and their stable derivatives, namely, endohedral metallofullerenes and exohedral derivatives, namely, endohedral metallofullerenes and exohedral fullerene fluorides, are generalised. The methods of synthesis and fullerene fluorides, are generalised. The methods of synthesis and purification of fullerene fluorides are considered and the strucpurification of fullerene fluorides are considered and the structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 97 publications
(284 reference statements)
0
16
0
2
Order By: Relevance
“…1, 2 The present review deals primarily with the energy aspects of fullerene fluorination. The results of studies of topochemical solid state fluorination (SSF) of [60]fullerene with inorganic variable valence transition metal fluorides are summarized.…”
Section: Methodsmentioning
confidence: 99%
“…1, 2 The present review deals primarily with the energy aspects of fullerene fluorination. The results of studies of topochemical solid state fluorination (SSF) of [60]fullerene with inorganic variable valence transition metal fluorides are summarized.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained results allow us to understand many features in the chemical formation of the families of these derivatives to explain quantitative differences in their synthesis and answer a number of questions arising in the course of the laboratory synthesis [21]. In particular, it is shown that absolute nullification of N DA , appearing as k reaches the value 24 for 60 fluorides, naturally explains the break in the corresponding series of the chemical synthesis on 60 F 48 molecule [4,5].…”
Section: Bases Of the Quantum Chemical Synthesis Of Fullerene Derivatmentioning
confidence: 99%
“…Well known reactions of hydration and fluorination of fullerenes in vapors of the corresponding gases are simplest from the computational viewpoint [4,5]. Let us exemplify the methods for such a synthesis by the initial phase of fluorination of 60 molecule.…”
Section: Bases Of the Quantum Chemical Synthesis Of Fullerene Derivatmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to this, the chlorination of C60 using iodine monochloride allowed the isolation of two fullerene chlorides, C60Cl6 [40] and C70Cl10 [41], characterized by NMR spectra. Finally, the fluorination of fullerenes using metal fluorides (among other fluorination agents) results in a wide range of adducts, from C60F2 to C60F48 [42][43][44][45]. Owing to their relatively high thermal stability, fluorofullerenes (contrary to chloro-and bromofullerenes) have been extensively investigated by electron impact (EI) mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%